Natural Compounds for Carcinoma Therapy by Wingless Signaling Pathway Down-regulation - Ojha, Smriti; Mishra, Rahul K.; Mishra, Sudhanshu; Singh, Amrita; Kumari, Shweta (Current Bioactive Compounds, 2023)
Cancer is a prominent cause of death that places a significant financial strain on the healthcare system. Because of its prevalence, there is unquestionably unmet need for new chemotherapeutics. Atypical activation and deregulation of the wingless (Wnt) signaling pathway are considered one of the major causes of various types of carcinomas. This receptor activation is directly correlated with the activation of β -catenin and β-catenin-dependent transcription. In the modern era of drug development, natural compounds have shown to be an unrivaled source of anticancer medications. Herbal compounds have been identified as potent β-catenin signaling inhibitors, mainly by their downregulation, modulating its phosphorylation, increasing ubiquitination and proteasomal destruction, blocking nuclear translocation, or other molecular mechanisms. In vitro and in vivo studies have revealed that these natural product inhibitors can prevent and treat cancer in a variety of cancer models. Natural products have the potential to be promising novel molecules for cancer treatment, making them an essential topic of study. The importance of natural products in blocking the numerous signaling pathways that promote carcinogenesis is explored in this review, paving the way for developing and discovering anticancer medicines.
Keywords: TNBC